Identifying On‐Surface Site‐Selective Chemical Conversions by Theory‐Aided NEXAFS Spectroscopy: The Case of Free‐Base Corroles on Ag(111). Issue 26 (23rd April 2018) - Aldahhak, H.; Paszkiewicz, M.; Rauls, E.; Allegretti, F.; Tebi, S.; Papageorgiou, A. C.; Zhang, Y.‐Q.; Zhang, L.; Lin, T.; Paintner, T.; Koch, R.; Schmidt, W. G.; et al.
Abstract: We demonstrate here that theory‐assisted near‐edge X‐ray absorption fine‐structure (NEXAFS) spectroscopy enables the site‐sensitive monitoring of on‐surface chemical reactions, thus, providing information not accessible by other techniques. As a prototype example, we have used free‐base 5, 10, 15‐tris(pentafluorophenyl)corroles (3H‐TpFPC) adsorbed on Ag(111) and present a detailed investigation of the angle‐dependent NEXAFS of this molecular species as well as of their thermally induced derivatives. For this, we have recorded experimental C and N K‐edge NEXAFS spectra and interpret them based on XAS cross‐section calculations by using a continuous fraction approach and core‐hole including multiprojector PAW pseudopotentials within DFT. We have characterized the as‐deposited low temperature (200 K) phase and unraveled the subsequent changes induced by dehydrogenation (at 330 K) and ring‐closure reactions (at 430 K). By exemplarily obtaining profound insight into the on‐surface chemistry of free‐base corrolic species adsorbed on a noble metal this work highlights how angle‐dependent XAS combined with accurate theoretical modeling can serve for the investigation of on‐surface reactions, whereby even highly similar molecular structures, such as tautomers and isomers, can be distinguished. Abstract : Theory‐assisted near‐edge X‐ray absorption fine‐structure (NEXAFS) spectroscopy enables the site‐sensitive monitoring of on‐surface chemical reactions, thus providing information not accessible by other techniques (see figure).